HUKUM JUAL BELI BAHAN SESEMBAHAN KEPADA PENYEMBAH BERHALA (PEKONG) MENURUT SYAIKH ZAINUDDIN ‘ABDUL ‘AZIZ AL-MALIBARIY (Studi Kasus Desa Bandar Klippa Kecamatan Percut Sei Tuan) - Sherly Maulina Brutu (ISLAMIC BUSSINESS LAW REVIEW, 2019)
The law of buying and selling materials for worship to idol worshipers (pekong) in the opinion of Shaykh Zainuddin ‘Abdul‘ Aziz Al-Malibariy is haraam. The sale and purchase of sacrificial material to the idol worshipers (pekong) in the village of Bandar Klippa, where many Muslim communities make buying and selling of worshiping material to the idol worshipers (pekong). The purpose of this study is to discuss several issues. First, how to carry out the sale and purchase of offerings to pagan worshipers (pekong) in Bandar Klippa Village, Percut Sei Tuan District. Secondly how is the opinion of Shaykh Zainuddin ‘Abdul‘ Aziz Al-Malibariy about the prohibited trading. Thirdly, how is the law of buying and selling materials for worship to idol worshipers (Pekong) in Bandar Klippa Village, Percut Sei Tuan District according to the perspective of Shaykh Zainuddin ‘Abdul‘ Aziz Al-Malibariy. The research method used in this study is a qualitative method in the form of field research (Field Research). The object determined in this research is the people in Bandar Klippa Village who carry out the sale and purchase of sacrificial material to the pekong (pekong) both sellers and buyers and are supported by data collection techniques by observation and interview and refer to the book Fathul Mu’in volume 2.